Pengaruh Budaya Korean Wave terhadap Peningkatan Hasil Belajar Pendidikan Agama Islam Siswa Kelas X SMK Yayasan Karya Pembangunan Pendidikan Bontang Tahun Pelajaran 2023/2024 - Faiqoh, Muslimatul; Ihsan, Muh (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
This study aims to determine the effect of Korean Wave culture on improving learning outcomes and improving Islamic Religious Education learning outcomes due to the influence of Korean Wave culture. This research uses quantitative methods. Data were collected through questionnaires distributed to grade X students, and analysed using descriptive and inferential statistical techniques to determine the effect of Korean Wave culture variables on Islamic Religious Education learning outcomes. The results showed that there was a significant positive effect of Korean Wave culture on improving Islamic Religious Education learning outcomes. Students who were exposed to Korean Wave culture showed increased motivation to learn, active participation in class, and better learning outcomes compared to students who were not exposed to the culture. Data analysis showed that exposure to Korean Wave culture improved comprehension of Islamic Education materials, increased students' engagement in class discussions, and improved their academic grades in Islamic Education subjects. This study concludes that Korean Wave culture has a positive impact on Islamic Religious Education learning outcomes of grade X students at SMK Yayasan Karya Pembangunan Pendidikan Bontang. Therefore, educators are advised to consider using relevant elements of popular culture in their teaching strategies to improve students' motivation and learning outcomes. This research also provides insights for schools and parents regarding the importance of understanding and utilising cultural trends that students are interested in to support a more effective and engaging learning process. This research also provides insights for schools, teachers, students and parents on the importance of understanding and utilising cultural trends that students are interested in to support a more effective and engaging learning process.